Pregnancy in sickle cell trait: what we do and don't know. (17th February 2020) - Wilson, Samuel; Ellsworth, Patrick; Key, Nigel S.
Summary: Sickle cell trait (SCT) is the carrier state for sickle cell disease that results from the HBB rs334 missense mutation (p.Glu6Val) in the β‐globin chain of haemoglobin. While not associated with any impact on life expectancy, it has been established that SCT is associated with an increased risk of both venous thromboembolism (and in particular, pulmonary embolism) and chronic kidney disease. It is largely unknown what short‐ or long‐term effect, if any, pregnancy has upon the risk or outcomes of these disorders. In addition, SCT has been linked with various adverse outcomes in pregnancy, ranging from maternal complications such as elevated risk of bacteriuria to potentially life‐threatening entities such as pre‐eclampsia and prematurity. In these scenarios also, no clear association with SCT has been established. Given the high worldwide prevalence of SCT, further studies addressing these issues are warranted.